発育予測モデルとメッシュ気象データを利用したダイズの乾燥ストレス発生リスクの広域評価 - 島田, 信二; 大野, 宏之; 中野, 聡史 (Seibutsu to kishou, 2017)
In this study, we aimed to estimate the drought vulnerability of soybeans in Japan based on meteorological factors in order to alleviate drought stress by introducing farm-oriented enhancement for aquatic-system (FOEAS). The differences between precipitation and crop evapotranspiration during the period from flowering (R2) to thirty days after the beginning of seed filling (R5) (WD) could be used to estimate decreases in the harvest index and seed yield with drought stress. This WD index was calculated to assess the occurrence of drought stress by considering the cultivars and cropping season in each region using long term (1980-2013) meteorological data and a phenological development model. The WD index was below zero about 50% of the time in the northern part of Fukui Prefecture with the assumption of Enrei cultivation. Moreover, our data showed that the WD index tended to decrease in northwestern Kyushu, where the Fukuyutaka cultivar predominated. Reference evapotranspiration tended to increase in many regions; however, in Saga City, located in northwestern Kyushu, precipitation tended to decrease, resulting in the decrease in the WD index in this region.